2010
DOI: 10.1016/j.pec.2009.11.010
|View full text |Cite
|
Sign up to set email alerts
|

The role of counseling for obstetric fistula patients: Lessons learned from Eritrea

Abstract: Objective The goal of this study was to evaluate the first formal counseling program for obstetric fistula patients in Eritrea. Methods To evaluate the impact of the counseling program, clients were interviewed both before pre-operative counseling and again after post-operative counseling. A questionnaire was used in the interviews to assess women's knowledge about fistula, self-esteem, and their behavioral intentions for health maintenance and social reintegration following surgical repair. In addition, two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 8 publications
2
34
1
Order By: Relevance
“…A study conducted in Eritrea among fistula patients established the need for a standardized counseling program for fistula patients (Turan et al, 2007). In a later study in Eritrea, Johnson et al (2010) demonstrated a significant and positive impact of a formal counseling program on fistula patients. The study aimed to evaluate the short-term impact of pre-and post-surgery counseling by trained counselors established that counseling improved patients' knowledge on fistula, improved their self-esteem, enhanced their mental health, and helped them have positive behavioral intentions (Johnson et al, 2010).…”
Section: Discussionmentioning
confidence: 95%
“…A study conducted in Eritrea among fistula patients established the need for a standardized counseling program for fistula patients (Turan et al, 2007). In a later study in Eritrea, Johnson et al (2010) demonstrated a significant and positive impact of a formal counseling program on fistula patients. The study aimed to evaluate the short-term impact of pre-and post-surgery counseling by trained counselors established that counseling improved patients' knowledge on fistula, improved their self-esteem, enhanced their mental health, and helped them have positive behavioral intentions (Johnson et al, 2010).…”
Section: Discussionmentioning
confidence: 95%
“…Thus, it is critical to establish systems that help women and their families understand the real risks of repeat fistula and the factors that may lead to it. There is a need for greater research on effective pre-and post-operative counselling programmes for fistula patients such as the one pioneered by Johnson et al (2010) in Eritrea. This study revealed promising results in promoting women's knowledge about fistula and its prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of depression in this population may therefore benefit from cognitive behavioural approaches (van’t Hof, Cuijpers, Waheed, & Stein, 2011), which could help to replace such thoughts with alternative medical explanations of the fistula. Although counseling interventions for this population exist (Gerten, Venkatesh, Norman, Shu’aibu, & Richter, 2009; Johnson et al, 2010), none utilise cognitive behavioural approaches within a religious framework. A religious framework that directly addresses religious and spiritual struggles that are experienced as a result of a stigmatised medical condition may be more salient in this setting than a purely secular framework (Tarakeshwar, Pearce, & Sikkema, 2005).…”
Section: Discussionmentioning
confidence: 99%